Reducing time from presentation to surgical intervention for testicular torsion: implementation of a quality improvement protocol - Richardson, Shannon; Huen, Kathy; Benga, Tabitha; Fajardo, Bridgette; Sturm, Renea; Lerman, Steven E.; Singer, Jennifer S. (Frontiers in Urology, 2024)
IntroductionTimely surgical intervention for patients with testicular torsion is a quality benchmark set by the U.S. News and World Report (USNWR) for pediatric urology. In this study, we describe and evaluate a quality improvement initiative to reduce the time to surgical intervention for testicular torsion at a single institution through the implementation of a clinical care pathway called “code torsion.”MethodsData abstraction was performed through retrospective chart review to assess process measures. Patients <21 years old with testicular torsion requiring surgical intervention were included. The clinical protocol “code torsion” was created by a multidisciplinary quality improvement workgroup with the primary goal of reducing the time from emergency department presentation to surgical intervention for testicular torsion. “Code torsion” was implemented in October 2021, which was assessed in addition to subsequent interventions through plan–do–study–act (PDSA) cycles.ResultsA total of 30 patients were identified prior to “code torsion” implementation and 14 thereafter. The mean time from triage to operating room (OR) was 228 min prior to “code torsion” compared with 180 min after protocol implementation (p = 0.047). The proportion of cases that had surgical intervention within the 4-h USNWR metric increased from 63% pre-protocol to 93% post-protocol (p = 0.07). Of the patients, 40% required orchiectomy prior to “code torsion” compared with 29% after implementation (p = 0.5). Patients requiring orchiectomy had a significantly longer time from symptom onset to surgical intervention (87 vs. 9.8 h, p < 0.001).ConclusionImplementation of the protocol “code torsion” was successful in reducing the time from presentation to surgical intervention for testicular torsion. The rates of testicular salvage did not differ after “code torsion” implementation and were instead found to be dependent on the total ischemia time.